OBTAINING THE SUITABLE TECHNIQUES FOR PALYNOLOGICAL PREPARATION - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2001)
The term of â€œstandard techniquesâ€ in preparation is no longer accepted since every sample has discrete characteristic which may require different treatment. Experiments prove that the modifications are needed to process the Eocene samples from Central Java and South Sulawesi.